2018
DOI: 10.1007/s00068-018-1020-x
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of flail chest or multiple rib fractures: current evidence and how to proceed. A systematic review and meta-analysis

Abstract: Purpose The aim of this systematic review and meta-analysis was to present current evidence on rib fixation and to compare effect estimates obtained from randomized controlled trials (RCTs) and observational studies. Methods MEDLINE, Embase, CENTRAL, and CINAHL were searched on June 16th 2017 for both RCTs and observational studies comparing rib fixation versus nonoperative treatment. The MINORS criteria were used to assess study quality. Where possible, data were poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 56 publications
4
98
1
1
Order By: Relevance
“…Furthermore, no difference was observed in effect estimates from RCTs and observational studies regarding the primary outcome measures. These results are in line with previous orthopedic trauma meta-analyses, [9][10][11][12] shown an increase of distal radius fractures in patients aged 17 to 64 years. 2 Hence, future studies should also focus on the nonelderly population, because traditionally most studies on this topic solely include patient populations 60 years or older.…”
Section: Jama Network Open | Orthopedicssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, no difference was observed in effect estimates from RCTs and observational studies regarding the primary outcome measures. These results are in line with previous orthopedic trauma meta-analyses, [9][10][11][12] shown an increase of distal radius fractures in patients aged 17 to 64 years. 2 Hence, future studies should also focus on the nonelderly population, because traditionally most studies on this topic solely include patient populations 60 years or older.…”
Section: Jama Network Open | Orthopedicssupporting
confidence: 92%
“…including RCTs and observational studies, showing high-quality observational studies to result in similar treatment effects compared with RCTs.Reports 9,[11][12][13][14][15]18 have shown that differences in effect estimates between RCTs and observational studies tend to be small. Randomized clinical trials require strict conditions such as participant selection, inclusion and exclusion criteria, randomization method, and outcome measurements.…”
mentioning
confidence: 99%
“…For certain type 3 comparisons an observational study design may therefore be suitable. Similar to type 2 comparisons, multiple recent meta-analyses where surgery was compared to conservative treatment indeed found that treatment groups appeared to be similar and effect estimates were comparable between observational studies and randomized trials [7][8][9]. In studies of type 3 comparisons, treatment groups may indeed be comparable if the surgeon's preference for one treatment option over the other is of greater influence on treatment decisions than (unmeasured) patient characteristics.…”
Section: Type 3: Comparison Of Surgical and Non-surgical Interventionmentioning
confidence: 87%
“…Provided observational studies are of high quality, adding information from observational studies to meta-analyses will increase the number of patients available for analysis and can lead to more precise effects estimates, possibilities for subgroup analysis, and may provide more insight in rare and longterm outcomes [7]. Obviously, only high quality observational studies should be included for meta-analysis, or at least sensitivity analysis, stratified by study quality, needs to be conducted [7][8][9]. Alternatively, statistical methodology has been developed to include external (observational) data in the analysis of randomized trials, that accounts for their (dis-)similarity [33,34].…”
Section: Combining Information Of Different Study Designsmentioning
confidence: 99%
See 1 more Smart Citation